Pension and Active Ageing: Lessons Learned from Civil Servants in Indonesia - Aris Ananta (MDPI AG, 2021)
Many developing countries are currently facing an ageing population without sufficient preparation for old-age financial adequacy, an important component in active ageing. One question is whether a pension system can create old-age financial adequacy. At the same time, many countries are shifting their pension systems from a defined benefit to a defined contribution pension system to improve the welfare of older people while maintaining state budget sustainability. Indonesia is not an exception. This paper learns from civil servants in Indonesia, where the retirement payout from the existing pay-as-you-go, defined benefit system is meagre. The system is to be transformed into a defined contribution one. Using a simulation method, this paper examines whether the proposed system will provide a better retirement payout, which is higher than the minimum wage and will allow retirees to maintain their pre-retirement income. This paper concludes that the proposed system alone is not sufficient to create old-age financial adequacy and, therefore, is less able to contribute to active ageing. To improve the retirement payout, among other things, the retirement age should be raised and made optional, and the accumulated savings should be re-invested during the retirement period.